Beatty Log Series - Correction
Paul C. Leopardi
leopardi at bigpond.net.au
Sat Jul 16 05:29:54 CEST 2005
Paul, reply below. Best regards, Paul Leopardi
On Fri, 15 Jul 2005 03:42 pm, Paul D. Hanna wrote:
> 1/[n(1+t)] - 1/[n(1+1/t)] - (1-t)/(1+t)/n
Lets call this term b(t,n).
By (1-t)/(1+t)/n do you mean:
1. [(1-t)/(1+t)]/n
(This is the interpretation used by Maple and most programming languages)
OR
2. (1-t)/[(1+t)/n] ?
With interpretation 1, we have
[(1-t)/(1+t)]/n = (1-t)/[n(1+t)]
and thus the whole expression b(t,n) is
b(t,n) = t/[n(1+t)] - 1/[n(1+1/t)]
= t/[n(1+t)] - t/[n(t+1)]
= 0 assuming that t is non-zero.
With interpretation 2, we have
b(t,n) = (1-t)/[n(1+t)] - (1-t)/[(1+t)/n]
= [(1-t)/(1+t)](n-1/n)
which will give a divergent sum when t does not equal 1.
More information about the SeqFan
mailing list